A reassessment of oil market volatility and stock market volatility: Evidence from selected SAARC countries - Tariq Aziz (Comparative Economic Research. Central and Eastern Europe, 2023)
Volatility spillover informs whether the information in one market impacts the information in another. This paper examines whether oil market volatility spills over to the equity markets of selected SAARC countries. The study uses data from February 2013 to September 2019 to obtain updated evidence about the transmission of global oil price volatility to the equity markets of the SAARC member countries. The bivariate EGARCH model is used to test for volatility transmission from the oil market to the stock market. It is found that oil price shocks do not significantly impact equity market volatility, except in Bangladesh. Policymakers can use these findings when making policy decisions.
Keywords: 330; stock market; oil market; volatility spillovers; information transmission; EGARCH